African marriage, between tradition and modernity : a socio-anthropological study of couple and marriage in the Gabonese culture - (:unkn) unknown (My University, 2012)
In Gabon, marriage is an institution which allows the union of two persons and two families. In legal terms, only the civil marriage has a legal value. But the traditional marriage still called usual marriage is an important step which takes place at the ceremony of the dowry. This study deals about the way Gabonese represent themselves the couple and the marriage.Our theoretical approach and our fields of investigation concern the sociocultural evolution of this institution and the relationship which the Gabonese establish between the culture, their behavior and their social actions. The interest here is to understand the influences there is with the western model of life in customs and lifestyle by means of the urbanization, the schooling and the media. Our problematic witch comes in several questions has for main objective to describe themodel and the type of couple the young people are expecting. About the work done in Gabon and France we can see a typology of behavior and speech collected. The main topics are : polygamy, dowry, mate choice, mixed couple, Aids, homosexuality and seduction. With their words, they have an special eye on Gabonese and French culture and have ashared speech between tradition and modernity. This work gives a new approach about couple relationships and marriage in a society in full evolution in Gabon.
Keywords: African Research